DNA methylation markers for early detection of women's cancer: promise and challenges. (June 2014) - Wittenberger, Timo; Sleigh, Sara; Reisel, Daniel; Zikan, Michal; Wahl, Benjamin; Alunni-Fabbroni, Marianna; Jones, Allison; Evans, Iona; Koch, Julian; Paprotka, Tobias; Lempiäinen, Harri; Rujan, Tamas; et al.
Breast, ovarian and endometrial cancers cause significant morbidity and mortality. Despite the presence of existing screening, diagnostic and treatment modalities, they continue to pose considerable unsolved challenges. Overdiagnosis is a growing problem in breast cancer screening and neither screening nor early diagnosis of ovarian or endometrial cancer is currently possible. Moreover, treatment of the diversity of these cancers presenting in the clinic is not sufficiently personalized at present. Recent technological advances, including reduced representation bisulfite sequencing, methylation arrays, digital PCR, next-generation sequencing and advanced statistical data analysis, enable the analysis of methylation patterns in cell-free tumor DNA in serum/plasma. Ongoing work is bringing these methods together for the analysis of samples from large clinical trials, which have been collected well in advance of cancer diagnosis. These efforts pave the way for the development of a noninvasive method that would enable us to overcome existing challenges to personalized medicine.